River Sand Replacement with Sustainable Sand in Design Mix Concrete for the Construction Industry - Akhtar, Mohammad N.; Alotaibi, Abdulaziz; Shbeeb, Nadim I. (Civil Engineering Journal, 2025)
The present study prepared four sustainable design mixes of concrete using desert sand, modified recycled sand, and supplementary cementitious material silica fume to replace cement. The design mix concrete was prepared using the absolute volume method of a design strength (f´c) and target strength (f´cr)of 30 MPa and 38 MPa, respectively. The analysis of results showed that the four sustainable design mix concrete successfully passed the strength criterion set by the ACI 318-19 building code. The resulting pattern shows an increment in the mechanical and durability properties compared to the reference mix when (50% desert sand + 50% recycled crushed sand) is combined with 5-12.5% silica fume. The optimum result was achieved when the optimized, sustainable sand ratio (50% desert sand + 50% recycled crushed sand) was combined with 10% silica fume. It can be concluded that the prepared concrete has excellent results in terms of concrete strength and durability properties. Furthermore, this study shows that 100% of natural sand and 10% of cement can be saved using the optimal proposed concrete design mix. This study would have explored sustainability in the Saudi region by utilizing a vast percentage of vacant desert sand in concrete manufacturing. Doi: 10.28991/CEJ-2025-011-01-012 Full Text: PDF